Cloud-Assisted Scalable Video Delivery Solution over Mobile Ad Hoc Networks - Lujie Zhong; Shijie Jia (International Journal of Distributed Sensor Networks)
Cloud computing is promising avenue for supporting high-performance and interactive streaming service. Making use of the clouds to flexibly increase the scale of video service system and provide fast search are key determinants for scalable mobile video streaming in order to ensure smooth playback experience. In this paper, we propose a novel Cloud-assisted Scalable Video Delivery Solution over mobile ad hoc networks (CSVD). CSVD makes use of the clouds to share responsibility for the load of resource management of media server, which supports fast resource searching and enhances system scalability. CSVD designs a new estimation model of resource maintenance scale in terms of quality of service- (QoS-) oriented dynamic balance between supply and demand, in order to economically use the clouds. A novel supplier scheduling algorithm that assigns resource suppliers for fast responding user request in terms of their load and serving capacity is proposed. Extensive tests show how CSVD achieves much better performance results in comparison with other state-of-the-art solutions.